2020
DOI: 10.3390/polym12081824
|View full text |Cite
|
Sign up to set email alerts
|

Dyeing of m-Aramid Fibers in Ionic Liquids

Abstract: Aramids represent a class of high-performance fibers with outstanding properties and manifold technical applications, e.g., in flame-retardant protective clothing for firefighters and soldiers. However, the dyeing of aramid fibers is accompanied by several economic and ecological disadvantages, resulting in a high consumption of water, energy and chemicals. In this study, a new and innovative dyeing procedure for m-aramid fibers using ionic liquids (ILs) is presented. The most relevant parameters of IL-dyed fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The meta/para aramid fibre are practically non‐dyeable in classic dyeing and printing procedures, after spinning, and the fibre itself has a pronounced yellow‐green colour which causes additional difficulties in dyeing 14,15 . Given the problematic nature of the application of traditional dyeing techniques, the literature finds research on the application of some treatments or process modifications 14,16–22 . Lei et al used disperse dyes of meta‐ and para‐aramid fibres using the N , N ‐diethyl m ‐toluamide as a carrier and good shade depth was achieved 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The meta/para aramid fibre are practically non‐dyeable in classic dyeing and printing procedures, after spinning, and the fibre itself has a pronounced yellow‐green colour which causes additional difficulties in dyeing 14,15 . Given the problematic nature of the application of traditional dyeing techniques, the literature finds research on the application of some treatments or process modifications 14,16–22 . Lei et al used disperse dyes of meta‐ and para‐aramid fibres using the N , N ‐diethyl m ‐toluamide as a carrier and good shade depth was achieved 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the para‐aramid fabric dyed with cationic dyes had good K/S values and good fastness properties 21 . Opwis et al, performed the dyeing of meta‐aramid fibres using ionic liquids as, so called, green solvent, and found that the textile samples show similar or even better results than conventionally dyed samples, showing optimal wash, light and rubbing fastness properties 22 . As for the vat dyes application, Kim et al dyed meta‐aramid fibres, finding that the colour yields are dependent upon dyeing temperature, liquor ratio, amount of reducing agent and salt.…”
Section: Introductionmentioning
confidence: 99%
“…Modern constructional polymers, especially composite materials, are often used in structural applications, where the ability to create properties such as stiffness, strength, or thermal conductivity makes them attractive compared with traditional engineering materials. Light and composite polymer materials were the subject of many research works and are used in various fields as support or load-carrying structures [2][3][4][5]. Materials engineering, also related to polymer composites formed on the basis of fabric and polymer coating, enables the production of materials with increased resistance to friction and wear [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Dyeing of polyester was carried out using ionic liquids such as 2-hydroxidiethanolamine as a dyeing medium (Andrade et al, 2017). Ionic liquids such as 1-ethyl-3-methylimidazolium ethyl sulfate, 1-ethyl-3-methylimidazolium diethyl phosphate, 1-ethyl-3-methylimidazolium chloride tributyl methylammonium methyl sulfate, 1-ethyl-3methylimidazolium acetate and tris (2-hydroxyethyl) methylammonium methyl sulfate were also used for the dyeing of polyester, polyester-cotton blend and polyamide fibres (Opwis et al, 2013). Processing of leather was carried out using various Deep Eutectic Solvents (Abbott et al, 2006).…”
Section: Introductionmentioning
confidence: 99%